Self-cutting: patient characteristics compared with self-poisoners. - Hawton, K; Harriss, L; Simkin, S; Bale, E; Bond, A (2004)
A large ( n = 14,892) consecutive sample of deliberate self-harm (attempted suicide) patients who presented to a general hospital in the United Kingdom during a 23-year study period was examined (over two consecutive time periods) in order to compare the characteristics of those who used self-cutting ( n = 428) and those who self-poisoned ( n = 11,065). Patients who used different methods on other occasions, or were not assessed by the psychiatric service, were excluded. In the first time period (January 1976-June 1988), the self-cutters were distinguished from the self-poisoners by more often being male, single, not employed, and having a history of previous deliberate self-harm. In the second time period (July 1988-December 1998) the self-cutters were again distinguished by more often being male and having a history of previous deliberate self-harm, but also by being more likely to live alone, misuse alcohol, and have low suicidal intent scores. The finding of an excess of males among the self-cutters is contrary to the impression in the literature that self-cutting presentations to general hospitals more often involve females. It also indicates that the treatment needs of those who deliberately cut themselves are likely to differ from those of self-poisoners.